Importance of sensorimotor training for injury prevention and athletic performance - Gollhofer, A.; Gruber, M. (Science and Skiing IV, 2008)
In the past decade several studies addressed the complex structure of sport related injuries. In large epidemiological and aetiological surveys it has been clearly demonstrated that damages to the ankle and knee joint are the most frequent injuries in many sport disciplines including alpine and nordic ski. Two types of injuries need to be separated: chronic injuries are related to long lasting overloads of specific biological structures, whereas acute injuries are determined by extrinsic and intrinsic risk factors that result in a harmful combination for a specific Situation.